Preparation method of high-content ardealite-based carbon sequestration cementing material
By mixing phosphogypsum with organic salt leach solution and carbonizing treatment under the action of ammonia water and carbon-oxygen gas, a high-dose phosphogypsum-based carbon-fixed gelling material was prepared, which solved the problem of insufficient dosage of phosphogypsum and low durability in green gelling materials, and achieved efficient resource utilization and CO2 fixation.
Patent Information
- Application Number
- CN202510003785.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-02
AI Technical Summary
When using phosphogypsum to prepare green gelling materials, excessive phosphogypsum cannot fully participate in the reaction, resulting in reduced cement strength and loss of durability, and it is difficult to achieve high resource utilization and large-scale application of phosphogypsum.
By preparing an organic salt leach solution and mixing it with phosphogypsum, adding ammonia water and passing it into carbon-oxygen gas for stirring, a carbonized phosphogypsum-based slurry was obtained, and then filtered and mixed with material A to prepare a high-dose phosphogypsum-based carbon-fixed gelling material.
The high dosage of phosphogypsum in gelling materials has been achieved, the unreacted residual amount of phosphogypsum is reduced, the compressive strength and durability are improved, and the fixation and storage of CO2 is achieved, which has good economic and social benefits.
Smart Images

Figure CN119898973A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material. Background Art
[0002] Using phosphogypsum to prepare building materials is currently a reliable way to utilize phosphogypsum as a resource. However, when using phosphogypsum to prepare green cementitious materials, phosphogypsum is often in excess. The excess phosphogypsum cannot fully participate in the reaction, and the residual phosphogypsum can only be wrapped by hydration products and exist in the cementitious material. After long-term contact with water, it will lead to a decrease in cement strength and a loss of durability.
[0003] In order to ensure the durability of cementitious materials, the dosage of phosphogypsum is usually controlled, which is not conducive to the high resource utilization and large-scale application of phosphogypsum. In addition, other materials (such as cement, mineral admixtures and additives) are also added to improve its performance. Compared with directly using cementitious materials with excellent performance, this method consumes more energy and resources and makes the process more complicated.
[0004] At present, phosphogypsum is used to prepare green cementitious materials, in which excessive phosphogypsum cannot fully participate in the reaction, and the phosphogypsum that does not participate in the hydration reaction can only be wrapped by the hydration product. After long-term contact with water, it will lead to a decrease in cement strength and loss of durability. In order to ensure durability, the dosage of phosphogypsum can only be controlled.
[0005] Therefore, the application of phosphogypsum in large amounts in green cementitious materials can achieve the fixation and storage of CO2, improve the resource utilization efficiency of phosphogypsum and reduce the damage of CO2 to the ecological environment. In the existing technologies for the utilization and carbon fixation of phosphogypsum, most studies convert calcium sulfate in phosphogypsum into calcium carbonate to achieve the consumption of phosphogypsum and the fixation of CO2, but it is difficult to use phosphogypsum combined with carbon fixation technology to prepare carbon fixation cementitious materials.
[0006] Patent document with announcement number CN118184184A discloses a low-carbon cementitious material with a large amount of steel slag composite phosphogypsum and a preparation method thereof. The cementitious material is made by mixing phosphogypsum, steel slag, slag and a small amount of additives from various industrial solid wastes in different industries. However, it fails to solve the technical problem of fixing and storing CO2. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material.
[0008] The present invention is achieved through the following technical solutions.
[0009] The present invention provides a method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material, comprising the following steps:
[0010] S1: preparing an organic salt leaching solution;
[0011] S2: uniformly mixing the organic salt leaching solution in step S1 with phosphogypsum to obtain phosphogypsum slurry;
[0012] S3: adding ammonia water to the phosphogypsum slurry obtained in step S2, and introducing carbon oxide gas into the supernatant and stirring, to obtain a carbonized phosphogypsum-based slurry;
[0013] S4: filtering the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and mixing the slag sample and the supernatant with material A to obtain a high-dosage phosphogypsum-based carbon-fixing cementitious material.
[0014] Preferably, in the step S1, one or more metal ion chelating agents are mixed and dissolved in water to obtain an organic salt leaching solution, and the metal ion chelating agents include one or more of amino acid derivatives, hydroxy acids, and organic polyphosphonic acids; in the step S2, CO2 gas is introduced into the supernatant and stirred for 4 to 6 minutes, and then allowed to stand at room temperature for a period of time to obtain phosphogypsum slurry.
[0015] Preferably, the components of the metal ion chelating agent for preparing the organic salt immersion solution include 80-83 parts of GA, 8-10 parts of EDTA-4Na, 1-2 parts of EDTMP, and 90-110 parts of water in parts by mass.
[0016] Preferably, in step S2, the phosphogypsum and the organic salt leaching solution are mixed in a liquid-to-solid ratio of 3:1 to 25:1, and the mixture is allowed to stand for >90 minutes to obtain a phosphogypsum slurry.
[0017] Preferably, the concentration of the ammonia water in step S3 is 25%, and the mass of the ammonia water is 10-40% of the dry mass of the phosphogypsum.
[0018] Preferably, in step S3, the delivery pressure of the carbon oxide gas is 0.1-8 MPa, the stirring speed is >700 r / min, and the time for introducing the carbon oxide gas is not less than 150 min.
[0019] Preferably, the pH value of the supernatant obtained after filtering the phosphogypsum slurry in step S4 is not less than 7.
[0020] Preferably, in step S4, material A includes mineral powder and quicklime. In parts by mass, 450-800 parts of slag sample, 300-500 parts of supernatant, 180-450 parts of mineral powder and 2-5 parts of quicklime are mixed to prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material.
[0021] Preferably, the mineral powder comprises granulated blast furnace slag powder of grade S95, S105, etc., and its specific surface area is not less than 400m 2 / kg.
[0022] Preferably, the quicklime has a calcium oxide content of not less than 95%.
[0023] The beneficial effects of the present invention are:
[0024] 1. Compared with ordinary Portland cement, the present invention reduces the process of "two grindings and one burning", greatly reduces energy consumption and greenhouse gas emissions. The present invention can directly utilize the original phosphogypsum without pre-treatment of the phosphogypsum, saves costs, improves the efficiency of resource utilization of phosphogypsum, provides direction and guidance for the treatment and utilization of bulk solid waste phosphogypsum, and has good economic and social benefits.
[0025] 2. Compared with traditional green cementitious materials, the high-dosage phosphogypsum-based carbon-fixing cementitious material of the present invention can fix and store CO2 while preparing the cementitious material, converting CO2 into inert carbonate substances in the high-dosage phosphogypsum-based carbon-fixing cementitious material, effectively fixing CO2, and facilitating sustainable green development.
[0026] 3. Compared with the existing phosphogypsum-based cementitious materials, the high-dosage phosphogypsum-based carbon-fixing cementitious materials of the present invention increase the dosage ratio of phosphogypsum in the cementitious materials, reduce the unreacted phosphogypsum residual amount in the phosphogypsum-based cementitious materials, and use the calcium carbonate obtained by the carbon fixation technology as a hydration product, so that the cementitious materials have better compressive strength and durability. The high-dosage phosphogypsum-based carbon-fixing cementitious materials of the present invention have a short preparation and molding time, a simple preparation method, are green and environmentally friendly, and have high resource utilization value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.
[0029] A method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material comprises the following steps:
[0030] S1: preparing an organic salt leaching solution;
[0031] S2: uniformly mixing the organic salt leaching solution in step S1 with phosphogypsum to obtain phosphogypsum slurry;
[0032] S3: adding ammonia water to the phosphogypsum slurry obtained in step S2, and introducing carbon oxide gas into the supernatant and stirring to ensure that the reaction is fully carried out to obtain a carbonized phosphogypsum-based slurry;
[0033] S4: filtering the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and mixing the slag sample and the supernatant with material A to obtain a high-dosage phosphogypsum-based carbon-fixing cementitious material.
[0034] In the step S1, one or more metal ion chelating agents are mixed and dissolved in water to obtain an organic salt leaching solution, and the metal ion chelating agents include one or more of amino acid derivatives, hydroxy acids, and organic polyphosphonic acids; in the step S2, CO2 gas is introduced into the supernatant and stirred for 4 to 6 minutes, and then allowed to stand at room temperature for a period of time to obtain phosphogypsum slurry.
[0035] The components of the metal ion chelating agent for preparing the organic salt immersion solution include 80-83 parts of GA, 8-10 parts of EDTA-4Na, 1-2 parts of EDTMP and 90-110 parts of water in parts by mass.
[0036] In step S2, the phosphogypsum and the organic salt leaching solution are mixed at a liquid-to-solid ratio of 3:1 to 25:1, and the mixture is allowed to stand for more than 90 minutes to obtain a phosphogypsum slurry. A too low liquid-to-solid ratio will reduce the leaching efficiency of calcium ions, while a too high liquid-to-solid ratio will lead to a waste of energy and resources.
[0037] In step S3, the concentration of ammonia water is 25%, and the mass of ammonia water is 10-40% of the dry mass of phosphogypsum. If the mass of ammonia water solution is too low, CO2 cannot be effectively captured, which easily leads to the escape of CO2, and the low reaction rate leads to low carbonization efficiency; if the mass of ammonia water solution is too high, the carbonization efficiency of calcium ions will no longer increase, which will cause waste of resources. When the CO2 pressure is too low, the reaction rate will be slow and the carbonization efficiency will be too low; when the pressure is too high, the carbonization of calcium ions will not be carried out in time, which will cause the escape and waste of CO2. If the CO2 introduction time is too short, the carbonization efficiency of phosphogypsum will be too low; if the introduction time is too long, the carbonization efficiency of phosphogypsum will be too high, and the acidic supernatant is not conducive to the coagulation and hardening of the cementitious material and the development of its performance.
[0038] In step S3, the delivery pressure of the carbon oxide gas is 0.1-8 MPa, the stirring speed is >700 r / min, and the time for introducing the carbon oxide gas is not less than 150 min.
[0039] The pH value of the supernatant obtained after filtering the phosphogypsum slurry in step S4 is not less than 7, which ensures that CO2 is fully dissolved and fixed, and ensures the alkaline environment required for the subsequent hydration reaction of the cementitious material.
[0040] In step S4, material A includes mineral powder and quicklime. In units of parts by mass, 450-800 parts of slag sample, 300-500 parts of supernatant, 180-450 parts of mineral powder and 2-5 parts of quicklime are mixed to prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material.
[0041] The mineral powder includes granulated blast furnace slag powder of grades S95 and S105, and its specific surface area is not less than 400m 2 / kg.
[0042] The quicklime is an alkaline activator for phosphogypsum-based slag cement, and its calcium oxide content is not less than 95%.
[0043] In step S4, carbon fixation is to convert the unstable phosphogypsum and some impurities therein into stable carbonate inert substances after carbonization.
[0044] Embodiment 1:
[0045] like Figure 1 As shown, a high-dosage phosphogypsum-based carbon-fixing cementitious material and a preparation method thereof, the specific steps are as follows:
[0046] S1: preparing an organic salt immersion solution, by mixing 80 parts of GA, 8 parts of EDTA-4Na, and 1 part of EDTMP, and fully dissolving them in 90 parts of water by mass to obtain an organic salt immersion solution;
[0047] S2: The organic salt leaching solution in step S1 and the original phosphogypsum are fully mixed and stirred at a liquid-to-solid ratio of 3:1 for 6 minutes, and allowed to stand at room temperature for 95 minutes;
[0048] S3: adding a 10% ammonia standard solution by dry basis weight of phosphogypsum to the phosphogypsum slurry obtained in step S2, and introducing CO2 gas into the supernatant at a delivery pressure of 0.5 MPa for 160 min and stirring at a constant speed of 750 r / min to ensure that the reaction is fully carried out;
[0049] S4: Filter the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and take 800 parts of the slag sample and 350 parts of the supernatant by mass, mix them with 185 parts of mineral powder and 2 parts of quicklime, and prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material after mixing. Pour it into a 40mm*40mm*40mm clean slurry mold, put it into standard curing after demoulding, and cure it to the specified age, and test the standard compressive strength. The mineral powder is S95 granulated blast furnace slag powder, and its specific surface area is not less than 400m 2 / kg.
[0050] The quicklime is an alkaline activator for phosphogypsum-based slag cement, and its calcium oxide content is not less than 95%.
[0051] Embodiment 2:
[0052] like Figure 1 As shown, a high-dosage phosphogypsum-based carbon-fixing cementitious material and a preparation method thereof, the specific steps are as follows:
[0053] S1: preparing an organic salt immersion solution, by mixing 81 parts of GA, 10 parts of EDTA-4Na, and 2 parts of EDTMP, and then fully dissolving them in 100 parts of water by mass to obtain an organic salt immersion solution;
[0054] S2: The organic salt leaching solution in step S1 and the original phosphogypsum are fully mixed and stirred at a liquid-to-solid ratio of 10:1 for 6 minutes, and allowed to stand at room temperature for 95 minutes;
[0055] S3: adding a 30% ammonia standard solution by dry basis weight of phosphogypsum to the phosphogypsum slurry obtained in step S2, and introducing CO2 gas into the supernatant at a delivery pressure of 2 MPa for 160 min and stirring at a constant speed of 750 r / min to ensure that the reaction is fully carried out;
[0056] S4: Filter the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and take 550 parts of the slag sample and 450 parts of the supernatant by mass, mix them with 340 parts of mineral powder and 3 parts of quicklime, and prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material after mixing. Pour it into a 40mm*40mm*40mm clean slurry mold, put it into standard curing after demoulding, and cure it to the specified age, and test the standard compressive strength. The mineral powder is S105 grade granulated blast furnace slag powder, and its specific surface area is not less than 400m 2 / kg.
[0057] The quicklime is an alkaline activator for phosphogypsum-based slag cement, and its calcium oxide content is not less than 95%.
[0058] Embodiment 3:
[0059] like Figure 1 As shown, a high-dosage phosphogypsum-based carbon-fixing cementitious material and a preparation method thereof, the specific steps are as follows:
[0060] S1: preparing an organic salt leaching solution, mixing GA, EDTA-4Na, and EDTMP in respective weight parts of 81, 9, and 2, and fully dissolving the mixture in 100 weight parts of water to obtain an organic salt leaching solution;
[0061] S2: The organic salt leaching solution in step S1 and the original phosphogypsum are fully mixed and stirred at a liquid-to-solid ratio of 20:1 for 6 minutes, and allowed to stand at room temperature for 95 minutes;
[0062] S3, adding a standard ammonia solution of 40% of the dry basis weight of phosphogypsum to the phosphogypsum slurry obtained in step S2, and passing CO2 gas into the supernatant at a delivery pressure of 5 MPa for 160 min and stirring at a constant speed of 750 r / min to ensure that the reaction is fully carried out;
[0063] S4: Filter the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and take 450 parts of the slag sample and 500 parts of the supernatant by mass, mix them with 450 parts of mineral powder and 5 parts of quicklime, and prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material after mixing. Pour it into a 40mm*40mm*40mm clean slurry mold, put it into standard curing after demoulding, and cure it to the specified age, and test the standard compressive strength. The mineral powder is S95 grade granulated blast furnace slag powder, and its specific surface area is not less than 400m 2 / kg.
[0064] The quicklime is an alkaline activator for phosphogypsum-based slag cement, and its calcium oxide content is not less than 95%.
[0065] The performance results of the carbonized phosphogypsum-based cementitious materials prepared in Examples 1 to 3 are shown in Table 1:
[0066] Table 1 Performance index results of Examples 1 to 3
[0067]
Claims
1. A method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material, characterized in that: The following steps are involved: S1: preparing an organic salt leaching solution; S2: uniformly mixing the organic salt leaching solution in step S1 with phosphogypsum to obtain phosphogypsum slurry; S3: adding ammonia water to the phosphogypsum slurry obtained in step S2, and introducing carbon oxide gas into the supernatant and stirring, to obtain a carbonized phosphogypsum-based slurry; S4: filtering the carbonized phosphogypsum-based slurry obtained in step S3 to obtain a slag sample and a supernatant, and mixing the slag sample and the supernatant with material A to obtain a high-dosage phosphogypsum-based carbon-fixing cementitious material.
2. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: In the step S1, one or more metal ion chelating agents are mixed and dissolved in water to obtain an organic salt leaching solution, and the metal ion chelating agents include one or more of amino acid derivatives, hydroxy acids, and organic polyphosphonic acids; in the step S2, CO2 gas is introduced into the supernatant and stirred for 4 to 6 minutes, and then allowed to stand at room temperature for a period of time to obtain phosphogypsum slurry.
3. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 2, characterized in that: The components of the metal ion chelating agent for preparing the organic salt immersion solution include 80-83 parts of GA, 8-10 parts of EDTA-4Na, 1-2 parts of EDTMP and 90-110 parts of water in parts by mass.
4. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: In the step S2, the phosphogypsum and the organic salt leaching solution are mixed in a liquid-to-solid ratio of 3:1 to 25:1, and the mixture is allowed to stand for >90 minutes to obtain a phosphogypsum slurry.
5. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: In step S3, the concentration of ammonia water is 25%, and the mass of ammonia water is 10-40% of the dry mass of phosphogypsum.
6. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: In step S3, the delivery pressure of the carbon oxide gas is 0.1-8 MPa, the stirring speed is >700 r / min, and the time for introducing the carbon oxide gas is not less than 150 min.
7. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: The pH value of the supernatant obtained after filtering the phosphogypsum slurry in step S4 is not less than 7.
8. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 1, characterized in that: In step S4, material A includes mineral powder and quicklime. In units of parts by mass, 450-800 parts of slag sample, 300-500 parts of supernatant, 180-450 parts of mineral powder and 2-5 parts of quicklime are mixed to prepare a high-dosage phosphogypsum-based carbon-fixing cementitious material.
9. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 8, characterized in that: The mineral powder includes granulated blast furnace slag powder of grades S95 and S105, and its specific surface area is not less than 400m 2 / kg.
10. The method for preparing a high-dosage phosphogypsum-based carbon-fixing cementitious material according to claim 8, characterized in that: The quicklime has a calcium oxide content of not less than 95%.
Citation Information
Patent Citations
Environment-friendly ardealite sound-absorbing board
CN103556736A
Protection method for improving soil slope to resist rainwater erosion through phosphogypsum and microorganisms
CN111424689A
Integrated process for flue gas desulfurization and denitrification and cementing material production
CN113117490A
Method for efficiently preparing fine calcium carbonate from ardealite
CN118289792A
Granulated Blast-furnace Slag Activator, Its Manufacturing Method Thereof, and Manufacturing Method of Cement
US20200299194A1